Ethylene Is Not Responsible for Phytochrome-Mediated Apical Hook Exaggeration in Tomato - Takahashi-Asami, Miki; Shichijo, Chizuko; Tsurumi, Seiji; Hashimoto, Tohru (Frontiers in Plant Science, 2016)
The apical hook of tomato seedlings is exaggerated by phytochrome actions, while in other species such as bean, pea and Arabidopsis, the hook is exaggerated by ethylene and opens by phytochrome actions. The present study was aimed to clarify mainly whether ethylene is responsible for the phytochrome-mediated hook exaggeration of tomato seedlings. Dark-grown 5-day-old seedlings were subjected to various ways of ethylene application in the dark as well as under the actions of red (R) or far-red light (FR). The ethylene emitted by seedlings was also quantified relative to hook exaggeration. The results show: Ambient ethylene, up-to about 1.0 μL L-1, suppressed (opened) the hooks formed in the dark as well as the ones exaggerated by R or FR, while at 3.0–10 μL L-1 it enhanced (closed) the hook only slightly as compared with the most-suppressed level at about 1.0 μL L-1. Treatment with 1-aminocyclopropane-1-carboxylic acid (ACC), the immediate precursor of ethylene biosynthesis, did not enhance the hook, only mimicking the suppressive effects of ambient ethylene. The biosynthesis inhibitor, CoCl2 or aminoethoxyvinylglycine, enhanced hook curvature, and the enhancement was canceled by supplement of ethylene below 1.0 μL L-1. Auxin transport inhibitor, N-1-naphthylphthalamic acid, by contrast, suppressed curvature markedly without altering ethylene emission. The effects of the above-stated treatments did not differentiate qualitatively among the R-, FR-irradiated seedlings and dark control so as to explain phytochrome-mediated hook exaggeration. In addition, ethylene emission by seedlings was affected neither by R nor FR at such fluences as to cause hook exaggeration. In conclusion, (1) ethylene suppresses not only the light-exaggerated hook, but also the dark-formed one; (2) ethylene emission is not affected by R or FR, and also not correlated with the hook exaggerations; thus ethylene is not responsible for the hook exaggeration in tomato; and (3) auxin is essential for the maintenance and development of the hook in tomato as is the case in other species lacking phytochrome-mediated hook exaggeration. A possible mechanism of phytochrome action for hook exaggeration is discussed.